A systematic analysis of genetic interactions and their underlying biology in childhood cancer - Josephine T. Daub (Nature Portfolio, 2021)
Josephine Daub, Saman Amini, et al. developed a genetic interaction map of childhood cancers by analyzing over 2,500 tumors from 23 types of childhood cancer. Their results provide a valuable resource for investigating the biological underpinnings of pediatric cancer.